2012
DOI: 10.1097/mca.0b013e32834f112a
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related deaths among different treatment options in chronic coronary artery disease

Abstract: Different treatment options for multivessel coronary artery disease have similar overall mortality: CABG patients had the lowest incidence of cardiac death, but the highest incidence of noncardiac causes of death, and specifically a higher tendency toward cancer-related deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…PCI is preferred when the malignancy is aggressive or widespread. CABG can be considered when the malignancy is potentially curable or when the estimated prognosis is acceptable .…”
Section: Invasive Evaluation and Management Of Cad In Cancer Patientsmentioning
confidence: 99%
“…PCI is preferred when the malignancy is aggressive or widespread. CABG can be considered when the malignancy is potentially curable or when the estimated prognosis is acceptable .…”
Section: Invasive Evaluation and Management Of Cad In Cancer Patientsmentioning
confidence: 99%
“…It has been shown that longterm mortality following CABG is mainly attributable to many causes, with a lowest incidence of cardiac death, but a highest incidence of noncardiac causes of death, and specifically a higher tendency towards cancer-related deaths. 5 Third, in this study, the regression analysis showed that the patients with renal function recovery after AKI had a decreased probability of long-term mortality. By the Kaplan-Meier method, moreover, the long-term mortality was directly related to the severity of AKI.…”
Section: Sirmentioning
confidence: 52%
“…5 Third, in this study, the regression analysis showed that the patients with renal function recovery after AKI had a decreased probability of long-term mortality. We are very interested in knowing whether studied populations include cancer patients.…”
mentioning
confidence: 52%
“…Çoğunlukla kardiyak iskemi daha önemli olduğu için baypas ilk olarak yapılır. Araştırmalar eş zamanlı ve aşamalı olarak opere edilen hastaların uzun süre takiplerindeki ölüm nedeninin, daha çok akciğer kanserine bağlı olduğunu göster-mektedir (23). İlk cerrahiden iki üç hafta sonra akciğer operasyonu önerilmektedir (20).…”
Section: İskemi̇k Kalp Hastaliklari Ve Akci̇ğer Hastaliklariunclassified